2016
DOI: 10.15405/epsbs.2016.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Emotional Intelligence and Academic Achievement in Adolescence: A Systematic Review

Abstract: Over the last decades, completion of compulsory education has become increasingly important due to labour market requirements of higher education personnel. There is a growing body of research suggesting associations between EI and scholastic success. The present paper focuses on the connection between emotional intelligence (EI) and academic performance in compulsory education, by examining the existent research. The rationale of the paper resides in the need of improving our understanding on the connection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several studies have shown that teachers require EI competency to support student learning, provide opportunities for social development, and promote academic achievement and success among students [83][84][85][86]. Similarly, EI competency can increase teachers' own work environment, psychosocial health, and well-being [87][88][89][90][91][92][93][94][95][96][97].…”
Section: Ei For Educational Developmentmentioning
confidence: 99%
“…Several studies have shown that teachers require EI competency to support student learning, provide opportunities for social development, and promote academic achievement and success among students [83][84][85][86]. Similarly, EI competency can increase teachers' own work environment, psychosocial health, and well-being [87][88][89][90][91][92][93][94][95][96][97].…”
Section: Ei For Educational Developmentmentioning
confidence: 99%
“…Designing and implementing EI development programmes for adolescent students might help educators to effectively identify students' emotional competencies, and needs and promote the growth of emotional skills in educational environment (Chis & Rusu, 2016) and enhance students' academic achievement (Adeyemo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was elucidated in the study as the level of emotional intelligence of the high school students is average their levels of academic achievement are also found to be average. Chis and Rusu (2016) examined existent research studies to understand the relation between emotional intelligence (EI) and academic achievement of adolescents aged between 12-20 years in public schools. Results of the reviewed studies revealed that i) most of the studies suggested a significant association between overall EI and academic achievement.…”
Section: Studies Related To Trait Emotional Intelligencementioning
confidence: 99%
“…Emotional intelligence has the potential to foster a conducive and constructive culture within the broader educational setting, characterized by enhanced positivity, support, and productivity. Educational institutions that place a higher emphasis on emotional intelligence (EI) have been seen to encounter a reduction in behavioral issues, enhanced teacher-student rapport, and elevated academic achievement (Chis & Rusu, 2016). The implementation of inclusive strategies, such as integrating social-emotional learning (SEL) curricula, has the potential to cultivate emotional intelligence throughout the educational setting, yielding advantages for students, educators, and the broader school community.…”
Section: Literature Reviewmentioning
confidence: 99%